Close correlation between global air temperature change and polar motion during 1962–2013. Issue 19 (7th October 2016) - Huang, Mei; Zhu, Lin; Gong, He; Shao, Yaping
Abstract: Polar motion is an important Earth orientation parameter, but our understanding of its relation to global climate change is highly uncertain. In this study, we examine the links between polar motion excitation and annual mean air temperature during the period of 1962–2013 and discuss the possible responsible mechanisms. The regions of positive correlation correspond well with the warming centers. Spectral analysis shows that they have strong signals at similar frequencies. Strong correlations are also found between the polar motion and surface air pressure and vertical integrated zonal wind. This implies that polar motion serves as an important indicator of global climate change, and thus, the feedbacks between the solid Earth and the climate system deserve careful considerations. Key Points: Strong correlation is found between the polar motion excitation and air temperature The changed distribution of atmospheric mass and angular momentum explains the strong correlation Polar motion is a powerful signal for global climate change